Early Operation for Complications Arising From Bariatric Surgical Tourism. Issue 8 (August 2022) - McKenzie, Jonathan Andrew; Drevets, Peter; Bolduc, Aaron; Greenberg, Jacob; Hilton, Lisa Renee
The patient is a 48-year-old female, who underwent LAGB in Tijuana, Mexico, via bariatric medical tourism in 2008. She had no follow up after surgery. Subsequently had a port infection, for which the port was removed, but the band was left in place. Suffered with chronic abdominal pain for many years before the retained band was recognized. During band removal, it was discovered that she had complete band erosion. After removal, her symptoms resolved. This case demonstrates the issues with bariatric medical tourism. Specifically, because of the lack of appropriate follow up. Follow up and monitoring after surgery is important for preventing bariatric surgery complications and assisting with adequate weight loss. The other aspect of the case is the importance to recognize bariatric surgery complications. Port infection should warrant an investigation for potential intra-abdominal sources. Band erosion is uncommon but known complication of LAGB and requires band removal.